2010
DOI: 10.1097/bot.0b013e3181f17a3b
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Detection of Subclinical Traumatic Cartilage Injury

Abstract: Objectives Post-traumatic arthritis is a major cause of disability. Current clinical imaging modalities are unable to reliably evaluate articular cartilage damage prior to surface breakdown, when potentially reversible changes are occurring. Optical Coherence Tomography (OCT) is a nondestructive imaging technology that can detect degenerative changes in articular cartilage with an intact surface. This study tests the hypothesis that OCT detects acute articular cartilage injury following impact at energy levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…Although cartilage surface changes have been shown to be well correlated with comprehensive tissue quality scores such as the Mankin score and therefore were focused on in previous OCT studies, the benefits of deeper tissue structural investigations have been demonstrated in a clinical context . Likewise, early‐stage OA is associated with subsurface changes in structural matrix properties of cartilage that may be superficially still intact, therefore tissue homogeneity was parameterized and quantified in the present study. While the association of homogeneity and biomechanics has been demonstrated previously, the present study's contrary findings may be due to differences in experimental setup, image analysis, parameter definition and extraction and cartilage characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cartilage surface changes have been shown to be well correlated with comprehensive tissue quality scores such as the Mankin score and therefore were focused on in previous OCT studies, the benefits of deeper tissue structural investigations have been demonstrated in a clinical context . Likewise, early‐stage OA is associated with subsurface changes in structural matrix properties of cartilage that may be superficially still intact, therefore tissue homogeneity was parameterized and quantified in the present study. While the association of homogeneity and biomechanics has been demonstrated previously, the present study's contrary findings may be due to differences in experimental setup, image analysis, parameter definition and extraction and cartilage characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…As yet, in vivo applicability of OCT has been demonstrated in the context of open knee surgery and arthroscopy . Further studies have investigated the potential of OCT in detecting early cartilage degeneration after concomitant meniscus damage or after mechanical injury . Recent studies have focused on the quantitative characterization of healthy and degenerative cartilage in terms of morphologic and optical parameters.…”
mentioning
confidence: 99%
“…5,29 Because arthroscopic surgery is invasive and limited to a subjective evaluation of softening of the intact articular surfaces of cartilage, improving the MRI evaluation of cartilage deep tissue may increase sensitivity to cartilage damage and early degeneration after ACL injuries. Ultrashort echo time (UTE) imaging is sensitive to short T2 signals (T2 <10 milliseconds) and has the potential to assess articular cartilage in the deep layers.…”
mentioning
confidence: 99%
“…One promising method is optical coherence tomography (OCT), which can be used transarthroscopically and is capable of quantitatively assessing surface topography, subsurface heterogeneity, and collagen orientation. These changes can be detected in articular cartilage with an intact surface prior to the development of macroscopic changes, and they correlate with quantitative MRI analyses 24,25 . Multiphoton microscopy also can detect three-dimensional structural changes similar to those seen with use of OCT, but it has the advantage of being capable of imaging down to the cellular level, which renders it the highestresolution in vivo imaging modality 26,27 .…”
Section: Imaging Of Osteoarthritismentioning
confidence: 69%